Selection of alternative material for common rail direct injection system - Senguttuvan, N.; Raja, S; Sasidharan, R. (International Journal of Engineering and Technology, 2014)
Common rail direct fuel injection is a modern variant of direct fuel injection system for petrol and diesel engines. The common rail system prototype was developed in the late 1960s by Robert Huber of Switzerland and the technology further developed by Dr. Marco. In petrol engine MPFI technology was developed and implemented in earlier days. Basically common rail tube was fabricated by steel for petrol engines. In the current study Steel, Brass, Aluminum alloy a356 and ABS materials were analyzed separately and aluminum is found the best material among the steel, brass and ABS material for common rail injection tube. Keywords: Common Rail Injection System, Alternate Material.